Analysis of the Influence of Macro Economic Factors on the Financial Performance of the Nadira Fashion Company in Randugunting Village, Bergas District, Semarang Regency - Waruwu, Mira Kritiani; Palupiningtyas, Dyah (Journal of Business Management and Economic Development, 2024)
This study investigates the relationship between macroeconomic factors and the financial performance of Nadira Fashion Company, located in Randugunting village, Bergas subdistrict, Semarang district. As a fundamental social necessity, clothing is intricately linked to daily life, with fashion trends evolving continually in the modern era. Despite its prominence, the fashion industry faces challenges influenced by macroeconomic conditions that impact company performance and value. Through path analysis utilizing data from banking financial reports and Indonesia's economic growth reports for 2021-2022, this research explores the impact of macroeconomic variables such as economic growth, inflation, interest rates, exchange rates, and government policies on Nadira Fashion Company's financial performance. The findings reveal that while fundamental macroeconomic factors may not significantly influence Nadira Fashion Company's financial performance or value, the company's internal financial metrics, notably profitability measured by return on equity (ROE), demonstrate a substantial positive correlation with company value. These results highlight the importance of considering company-specific factors alongside macroeconomic variables in assessing financial performance and value in the fashion industry. The study provides valuable insights for investors, policymakers, and business managers, aiding in strategic decision-making and risk management. Ultimately, by understanding the interplay between macroeconomic conditions and company dynamics, stakeholders can navigate challenges effectively and capitalize on opportunities for sustainable growth in the fashion sector.